PENGAWASAN DINAS SOSIAL DAN TENAGA KERJA TERHADAP PEMENUHAN HAK TENAGA KERJA PADA PERUSAHAAN DI KABUPATEN KAMPAR TAHUN 2014/2015 - Andyka Anizur; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at Social Service and Labor of Kampar Regency and some related places in the research. The aim of this study is to determine the performance of the supervision of the Social Service and Labor of Kampar Regency toward labor rights in 2014/2015. This research is descriptive research, that is research looking for variable value without connecting variable one with other variable. Data collection in this research is done by in-depth interview to resource person.The result of descriptive analysis on the supervision of Social Service and Labor of Kampar Regency is the supervision done indirectly and directly. Indirect supervision is done by obligatory report from every company. Direct supervision is done by coming directly to supervise in related companies. In conducting supervision, Social Service and Labor of Kampar Regency experienced inhibiting factor that is the number of functional supervisory staff that is not sufficient where 50 companies should be supervised by 1 supervisor and accompanied by functional supervisory staff in Kampar Regency whose not yet PPNS. Based on the result of this research, it can be concluded that the supervision done by the Social Service and Labor of Kampar Regency is still not effective and efficient in reaching its target.Keyword : Supervision, Labor Rights